DEVELOPMENT OF INCLUSIVE SOCIETY WITH THE INSTRUMENTS OF “GREEN” ECONOMY AND EDUCATION (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
The article substantiates that in order to ensure the effective development of economic systems, the issues of rational use of natural resources and environmental safety are significant. Environmental problems for modern economies of the world are systematized. The aim of the research is to study the theoretical and practical experience in the formation of an inclusive society and the “green” economy of the regions in the Republic of Belarus based on the analysis of the mechanism for introducing circular technologies at the micro level, schemes for engaging vulnerable groups of the population, creating “green” jobs, creating courses on the principles of inclusion economy in the workplaces. The following tasks were set and resolved: the mechanism for the formation of the inclusive society and the “green” economy in the Republic of Belarus was identified through the introduction of circular technologies at the micro level; considered the features of involvement in employment of vulnerable groups of the population; identified and systematized features of creating “green” workplaces; specificity of courses for on-the-job training on the principles of inclusion and “green” economy is grounded. The research methodology is based on the principles of systems analysis, formal logic and an interdisciplinary scientific approach. Monographic and descriptive method was used in the formation of theoretical and practical basis for development an inclusive society with elements of the “green” economy; method of analysis and synthesis, method of statistical data analysis in the short-term analysis. The novelty of this research lies in the fact that the theoretical and practical foundations for building the inclusive society through the tools of the “green” economy and education have been studied and scientifically grounded. The conclusions are that the creation of “green” jobs, learning the principles of a “green” economy, as well as the implementation of other measures to ensure the sustainable development are necessary. And development of inclusive society and “green” economy depend on ability of government and firms to teach their basic principles and create inclusive and “green” workplaces and jobs. As recommendations it is proposed to involve older labor resources in employment, taking into account coordination of the vocational qualification structure of labor supply and technical and technological parameters of workplaces; to assess development of the international labor market and sustainable development of the labor market with created by authors list of indicators; to develop an electronic web resource with information about the skills of the workforce, indicating the geography of workplaces and schemes for building up the necessary skills contributes to the advance preparation of the workforce; and to organize and conduct courses for employers and employees in the field of inclusive development and “green” jobs.